BALI WOMEN'S CAREER DEVELOPMENT: A PSYCHOLOGICAL PERSPECTIVE - Yeyen Komalasari (Jurnal Ekonomi dan Bisnis Jagaditha, 2018)
Virtually, here are many factors affecting the career development of women, both external and internal factors (psychological). But researchers rarely discuss about fear of success as the most influential psychological factors on women's career development. Lately there have been many women leaders who indicated that women's career development is improving. Some literature and empirical research show that the higher the fear of succsess the lower the female spirit to compete for achievement, thus affecting the slow development of a woman's career, but there is also an opinion that the fear of success does not affect the development of a woman's career. It can be said that this difference of opinion is important to be examined, so that it can explain the real situation that happened to a woman career in Bali. This study aims to explain the process and mechanism of fear of success as a psychological factor affecting the career of women especially in Bali. Research method used in this study was qualitative research. The practical implication is that women are able to understand themselves internally psychological, so they could have the confidence in achieving success in the development of their careers. It is expected that companies and governments understand and tolerate women from the psychological side they experience. The orisinality statement on that Balinese women have the fear of success but can overcome it well because they obtains support from religious teachings or beliefs which is a deeply rooted cultural reflection and support from the family.